The Polymorphism Study of LEP and LEPR Genes in Association of its Serum Level in Iraqi Patients with Type 2 Diabetic - Nawfal Hussein Amhe, Fawzi Hassan Zayr Al-Fahdawi, Ali Gheisarzadeh, A.A Hatamnia (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes is a major cause of mortality worldwide. There are several types of diabetes, with type 2 diabetes mellitus (T2DM) being the most common. Many factors, including environmental and genetic factors, are involved in the etiology of the disease. Numerous studies have reported the role of genetic polymorphisms in the initiation and development of T2DM. Aim of study to investigate the prevalence of single nucleotide polymorphisms in LEP gene (LEP 3′UTR A/C, −2548 G/A) and LEPR (K109R and Q223R) and their association with Leptin level and obesity Methods: Here we recruited 150 patients with T2DM and 150 normal individuals. Genotyping was performed using polymerase chain reaction‐restriction fragment length polymorphism, BMI was calculated, and Leptin level was measured by ELISA. The polymorphism study was performed At Leptin -2548G/A and Leptin receptor LEPR Q223R. Statistical analyses were performed by spss19.0. Results: Our data showed that there was a significant difference between BMI, HbA1c, Cholesterol, TG, HDL, LDL and Leptin level in T2DM and normal group, however there was no significant difference in gender of all individuals in two groups of T2DM and normal groups. The G-allele frequency was found to be significantly different between T2DM and control groups. In addition, the genotypic and allele frequencies of Leptin receptor LEPR Q223 Polymorphism in the study individuals have been presenteted. The Q-allele frequency was found to have no significant difference between T2DM and control groups. Our data clearly indicated that HbA1c significantly related with BMI. Similarly cholesterol level significantly related to BMI and HbA1c. There was a similar pattern between other parameters. However there were no significant relationship between HDL and other lipid profile. Moreover, the concentration of Leptin was 5.74± 1.27, 5.67± 1.24 And 4.09 ± 1.44 For genotypes of QQ, QR and RR, respectively. However there was no significant difference in normal group. Conclusion: We found a significant association between the LEPR gene polymorphism and increased T2DM risk in the Iraqi population. Iraqi carriers of the G allele of LEPR gene polymorphism may be more susceptible to T2DM.